Correction of vitamin D level in young children with recurrent episodes of broncho-obstructive syndrome - K.K. Godjacka (Zaslavsky O.Yu., 2018)
Background. Predisposition to frequent acute respiratory viral infections (ARVI), in particular recurrent course of broncho-obstructive syndrome (BOS), in young children remains an important issue in pediatrics. Special attention has been recently paid to studying the level of vitamin D (VD, 25(OH)D) among other risk factors of recurrent episodes of BOS. Recent studies demonstrate a correlation between low levels of VD and increased susceptibility to viral infections. At the same time, the issue of studying the need to correct VD status in children with recurrent BOS is still unexplored. Thus, the purpose of the research was to study VD level and effectiveness of correction of its disturbances in young children with recurrent episodes of BOS. Materials and methods. We examined 120 children aged 6 months to 3 years with a clinical diagnosis of acute obstructive bronchitis. Patients were divided into two groups (group I - 60 children with episodic BOS (less than 3 episodes per year), group II - 60 children with recurrent BOS (3 and more episodes per year)). The control group consisted of 30 clinically healthy children aged from 6 months to 3 years. All patients were evaluated for anamnestic data, including those that affect VD. The concentration of 25-hydroxyvitamin D (25(OH)D) in the blood serum was determined by an electrochemiluminescence method on the Cobas e411 analyzer (serial number 1041-24, manufactured by Roche Diagnostics GmbH, Germany). We chose 30 patients from a group with recurrent BOS by a simple randomization, they received 1,000 IU of vitamin D3 daily during the year, except summer. The duration of follow-up was 12 months. The effectiveness of vitamin D3 was evaluated based on the dynamics of respiratory morbidity, incidence of BOS episodes and dynamics of serum level of 25(OH)D. Nonparametric statistical criteria were used in the analysis of the obtained data. The difference between compared indicators was considered to be significant at a rate of p < 0.05. Results. Most patients with a recurrent course of the disease (56.6 %) had 4 episodes of BOS for the last 12 months. The mean 25(OH)D serum level in children of group I was 33.0 (28.19; 41.97) ng/ml and group II - 13.68 (7.96; 19.51) ng/ml (p < 0.001). The analysis of anamnestic parameters that affect VD level showed that the probability of VD insufficiency or deficiency in young children with BOS who are not receiving vitamin D is much higher than in children who is taking it daily at a dose of 500-1,000 IU (odds ratio = 0.047; 95% confidence interval 0.018-0.126; p < 0.001). The inverse relationship was revealed between VD level and both the incidence of BOS (r = -0.27, p = 0.002) and the age of examined patients (r = -0.33, p = 0.009). The average incidence of episodes of acute respiratory infections in children of group II for the last year was higher than that of patients in group I (4.5 (3.0; 5.5) and 3 (2.0; 5.0), respectively, p < 0.001). We found that the mean 25(OH)D level tended to be lower in the presence of 5 or more episodes of ARVI per year. In most patients after taking vitamin D3, the incidence of BOS was reduced to 1-2 episodes per year, and respiratory morbidity decreased by 50 %. We revealed that after vitamin D3 supplementation, 25(OH)D level was significantly increased as compared to that of determined at baseline (25.11 (12.14; 42.47) ng/ml and 13.93 (9.60; 20.5) ng/ml, respectively, p = 0.002 according to the Wilcoxon T test). Conclusions. The majority of patients with recurrent BOS has VD deficiency that might be considered as a predictor of recurrent episodes of the disease. VD content is mostly dependent on the level of its supplementation. It is important to assess anamnestic data about using vitamin D and if necessary to determine serum level of 25(OH)D in young children who are often suffer from ARVI, including recurrent BOS. It has been established that in case of decreased serum concentration of 25(OH)D, the number of BOS and ARVI episodes increases. Also, VD level tends to be lower with increasing age. A daily intake of 1,000 IU of vitamin D3 for 12 months contributes to a decrease in ARVI incidence, including episodes of BOS, in young children.